Penentuan Jenis Trasportasi Pengiriman Beras untuk Efisiensi Biaya dengan Metode Heuristik - Eddi Indro Asmoro; Antono Adhi; Enty Nur Hayati (Jurnal Ilmiah Dinamika Teknik, 2008)
Transportation model will transform some m sources to n goals. To choose transportation tools, it is necessary to develop a software in order to get optimum solution. Heuristic methode, Generate and Test is used to gain transportation tools with minimum cost. This program will be developed in Visual Basic. Result of Generate and Test methode is optimum combination of transportation tools get from comparing every combination with other combination.